The Eskimo and the oil man : the battle at the top of the world for America's future - Reiss, Bob (New York : Business Plus, 2012)
Looks at the situation being created by the melting ice in the Arctic revealing new sites for offshore drilling, seen through the eyes of two disparate figures, an Alaskan Eskimo leader and the head of Shell Oil's Alaska venture.
Includes index.
Keywords: Itta, Edward; Itta, Edward; Shell Oil Company; Shell Oil Company; Petroleum industry and trade -- Alaska; Petroleum reserves -- Alaska; Eskimos -- Land tenure -- Alaska; Offshore oil well drilling -- Alaska; Petroleum industry -- Alaska; Petroleum -- Alaska; Land tenure -- Alaska; Inuit -- Alaska; Offshore oil well drilling -- Alaska